ANALISIS PERBANDINGAN PENGARUH VARIABEL MAKRO EKONOMI TERHADAP STABILITAS BANK SYARIAH DAN BANK KONVENSIONAL DI INDONESIA PERIODE TAHUN 2010-2017 - Fajar Fairuzy Sadrinata; Lina Nugraha Rani (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The research aims to identify and analyze the partial and simultaneous influence of macroeconomic variables consisting of inflation, GDP, balance of payments, and BI interest rates on the stability of Sharia banks and conventional banks in Indonesia. The research also aims to analyse the differences in macroeconomic variables to influence the stability of banking between sharia banks and conventional banks in Indonesia. The research was based on comparisons of the influence of stability between sharia banks and conventional banks on the macroeconomic variables investigated. The population in this research is sharia Bank and conventional Bank in Indonesia issued by OJK, sharia Bank statistics and conventional Bank. The analytical techniques used are statistical analyses. The analysis of data in this study uses two phases, namely descriptive statistics and inferential statistics.Keywords: inflation, GDP, payment balance, BI interest rates